Implementasi SCRUM Agile Pada Rancang Bangun E-Commerce - Paisal (JSAI (Journal Scientific and Applied Informatics), 2025)
E-Commerce is an application that supports buying and selling activities using internet media so that many people can access it. the development of complex e-commerce systems requires an effective project management approach to produce products that meet user needs and are completed optimally. Agile methods, especially SCRUM, are becoming an increasingly popular choice in software development, including for e-commerce projects. The SCRUM method is applied in several sprints, which include planning, development, testing, and evaluation stages. After several sprints were completed, Integration Testing was conducted to evaluate system performance and integration between modules, such as user login, product management, shopping cart, checkout, and payment gateway. Based on the results of Integration Testing, the e-commerce system developed with the SCRUM method shows a success rate of 91%.